Teori Pengetahuan Dalam Pendidikan - Situmorang, Efi Yanita (Journal of Innovation in Teaching and Instructional Media, 2025)
Science is a system created through the process of observation, experimentation, and analysis, whose existence is based on human curiosity, which continues to seek answers to all events, Science continues to develop until now and is able to meet all human needs in all areas of life, including education. The purpose of this article is to provide a comprehensive explanation of various theories of knowledge and their implications for educational practices in schools and universities. This research method is a library research method or Literature Research. Data were collected through research, examination, review of 15 journals relevant to this discussion. The findings of this article outline the fundamental foundations of the theory of knowledge and its application in the world of education to create a learning environment that supports students’ cognitive and social development. Educators are expected to understand theories of knowledge so that they can design learning strategies that are more effective and relevant to students’ learning needs.